1970
DOI: 10.1111/j.1744-7348.1970.tb04565.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between nutrients in extracted xylem sap and the susceptibility of fruit trees to silver‐leaf disease caused by Stereum purpureum (Pers.) Fr.

Abstract: S U M M A R YXylem sap was extracted from cut branches of stone-fruit and pip-fruit trees at different times of the year, and analysed for nitrogen and carbohydrate content. Growth of Stereumpurpureum was measured in the different sap samples in vitro. Nitrogen and carbohydrate levels in xylem sap from peach trees were highest in late winter and early spring, and these samples supported most growth of S. purpureum. At full bloom the levels of nitrogen and carbohydrate in xylem sap from stone-fruits (peach, nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…purpureum was increasing (Dye 1967;Beever 1970). Thirty trees were pruned using modified secateurs described in the Appendix and each cut was sprayed immediately with 0.8% captafol (I % Difolatan 80 wp in water) until completely wet.…”
Section: Experiments On Nursery Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…purpureum was increasing (Dye 1967;Beever 1970). Thirty trees were pruned using modified secateurs described in the Appendix and each cut was sprayed immediately with 0.8% captafol (I % Difolatan 80 wp in water) until completely wet.…”
Section: Experiments On Nursery Treesmentioning
confidence: 99%
“…Fr. Pruning is frequently carried out in July and August when weather conditions are often highly favourable for spore release by C. purpureum (Dye 1974) and for the establishment of infections (Brooks & Moore 1926;Dye 1967;Beever 1970). Prompt application of antimicrobial paints, e.g., 'Prunteci', on the pruning cuts is an effective method of wound protection (Dye 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Little has been published concerning the infection process of C. purpureum., except that it occurs mainly within xylem tissues, particularly within the lumen of xylem vessels and that nutrients are obtained from xylem sap (BINTNER 1919;BEEVER 1970). Also, basidiospores are thought to be sucked a considerable distance into vessels by the transpiration stream (BROOKS and MOORE 1926).…”
Section: Introductionmentioning
confidence: 99%
“…BROOKS and MOORE (1926) showed that fresh wounds on pear trees were highly susceptible to infection whereas it was very difficult to infect month old wounds and impossible to infect three month old wounds. Also there are reports (BROOKS and MOORE 1926;DYE 1967;BEEVER 1970) that the susceptibility of various host genera to C. purpureum varies throughout the year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation